Millennial perceptions of Airbnb in Kota Kinabalu, Sabah - Istekhar Ahmad, Nazmeen Fatima; Alias, Nur Izzati Nabilah; Mohamad Faizal, Adriana; Mohd Zaidi, Nur Murniza; Mohamad Musa, Nurafiqah; Gatu, Alvin (Universiti Teknologi Mara Cawangan Pulau Pinang, 2023)
Over the years, a peer-to-peer (P2P) accommodation service known as Airbnb has grown significantly in Malaysia. Airbnb has unique features that distinguish it from existing markets, such as traditional hotels, as it purchases and exchanges goods. Airbnb allows visitors from all over the world to make reservations from a list of registered hosts. Nevertheless, there is a lack of studies done related to millennial perceptions of the existence of Airbnb. Therefore, this study highlighted the relationship between authentic experience, social benefits, trust in Airbnb, and relative attractiion with millennial perceptions of Airbnb in Kota Kinabalu, Sabah. A descriptive research design with a quantitative approach was used to collect the data and the study focused on the millennials in Kota Kinabalu, Sabah within the age range of 25 to 40 years of age as the population representative of millennials. The data collected through this online survey questionnaire is tabulated using Statistical Package for Social Sciences (SPSS). According to the results of the tests, all hypotheses were found to have a positive impact on the millennials' perception to use Airbnb services. Based on the data, it can be inferred that millennials in Kota Kinabalu are likely to continue and use Airbnb services in the future because their impressions of the service are extremely positive.